Do reductions in agricultural field drainage during the growing season impact bacterial densities and loads in small tile-fed watersheds?. (15th March 2019) - Wilkes, G.; Sunohara, M.D.; Topp, E.; Gottschall, N.; Craiovan, E.; Frey, S.K.; Lapen, D.R.
Abstract: Predicting bacterial levels in watersheds in response to agricultural beneficial management practices (BMPs) requires understanding the germane processes at both the watershed and field scale. Controlling subsurface tile drainage (CTD) is a highly effective BMP at reducing nutrient losses from fields, and watersheds when employed en masse, but little work has been conducted on CTD effects on bacterial loads and densities in a watershed context. This study compared fecal indicator bacteria (FIB) [ E. coli, Enterococcus, Fecal coliform, Total coliform, Clostridium perfringens ] densities and unit area loads (UAL) from a pair of flat tile-drained watersheds (∼250–467 ha catchment areas) during the growing season over a 10−year monitoring period, using a before-after-control-impact (BACI) design (i.e., test CTD watershed vs. reference uncontrolled tile drainage (UCTD) watershed during a pre CTD intervention period and a CTD-intervention period where the test CTD watershed had CTD deployed on over 80% of the fields). With no tile drainage management, upstream tile drainage to ditches comprised ∼90% of total ditch discharge. We also examined FIB loads from a subset of tile drained fields to determine field load contributions to the watershed drainage ditches. Statistical evidence of a CTD effect on FIB UAL in the surface water systems was not strong; however, there was statistical evidence of increased FIB densities [pronounced when E. coli >200 most probable number (MPN) 100 mL −1 ] in the test CTD watershed during the CTD-intervention period. This was likely a result of reduced dilution/flushing in the test CTD watershed ditch due to CTD significantly decreasing the amount of tile drainage water entering the surface water system. Tile E. coli load contributions to the ditches were low; for example, during the 6-yr CTD-intervention period they amounted to on average only ∼3 and ∼9% of the ditch loads for the test CTD and reference UCTD watersheds, respectively. This suggests in-stream, or off-field FIB reservoirs and bacteria mobilization drivers, dominated ditch E. coli loads in the watersheds during the growing season. Overall, this study suggested that decision making regarding deployment of CTD en masse in tile-fed watersheds should consider drainage practice effects on bacterial densities and loads, as well as CTD's documented capacity to boost crop yields and reduce seasonal nutrient pollution. Graphical abstract: Image 1 Highlights: Free tile drainage contributed ∼90% (avg.) flow to stream during growing season. When controlling tile drainage, tile flow contributions to stream were ∼43% (avg). Fecal indicator bacteria loads did not reduce with reduced field drainage. E.coli densities in stream increased due to reduced field drainage. Contributions of FIB from field to stream were very small overall (∼11% avg.)